Experimental investigation of shear strength of full-scale concrete slabs subjected to concentrated loads in nuclear buildings. (15th January 2017) - Bui, T.T.; Abouri, S.; Limam, A.; NaNa, W.S.A.; Tedoldi, B.; Roure, T.
Highlights: In these experiments, 9 large scale specimens of RC slabs were tested. An increase in shear strength with increasing compressive strength was observed. No clear influence of the reinforcement was found. The maximum aggregate size improved the shear strength. Arching action was present in the free shear spans between 0.5 d and 2 d . The EC2 using the French Annex gave the best predictions. Abstract: The following study analyzes the shear behavior of full-scale slabs without shear reinforcement (the design of slabs used in nuclear buildings) under a concentrated load near a linear support. Experimental tests were conducted to quantify the shear strength and the associated failure modes. We addressed the influence of several variables, such as bottom longitudinal reinforcement, bottom transverse reinforcement, compressive strength, concrete aggregate size, and influence of the slab depth. A series of ten tests on nine full-scale slabs (one slab of 3.2 m × 2.9 m × 0.3 m; six slabs of 4 m × 2.6 m × 0.3 m; one slab of 4 m × 2.6 m × 0.35 m; one slab of 4 m × 2.6 m × 0.4 m) are presented. Realistic boundary conditions with the slabs supported on all four sides were used. The experiments are firstly used to evaluate the pertinence of Eurocode 2 for the shear design of reinforced concrete slabs without shear reinforcement in comparison with the French approach, and then to make comparisons with the ACI 318-14 code. We also studied the verification of a new proposal for the extension of Eurocode 2 proposed by Lantsoght et al. (2015).